Vegetation Succession, Carbon Accumulation and Hydrological Change in Subarctic Peatlands, Abisko, Northern Sweden - Gałka, M; Szal, M; Watson, EJ; Gallego-Sala, A; Amesbury, MJ; Charman, DJ; Roland, TP; Edward Turner, T; Swindles, GT (Permafrost and Periglacial Processes, 2017)
This is the author accepted manuscript. The final version is available from Wiley via the DOI in this record. High-resolution analyses of plant macrofossils, testate amoebae, pollen, mineral content, bulk density, and carbon and nitrogen were undertaken to examine the late Holocene dynamics of two permafrost peatlands in Abisko, Subarctic Sweden. The peat records were dated using tephrochronology, 14C and 210Pb. Local plant succession and hydrological changes in peatlands were synchronous with climatic shifts, although autogenous plant succession towards ombrotrophic status during peatland development was also apparent. The Marooned peatland experienced a shift ca. 2250 cal yr BP from rich to poor fen, as indicated by the appearance of Sphagnum fuscum. At Stordalen, a major shift to wetter conditions occurred between 500 and 250 cal yr BP, probably associated with climate change during the Little Ice Age. During the last few decades, the testate amoeba data suggest a deepening of the water table and an increase in shrub pollen, coinciding with recent climate warming and the associated expansion of shrub communities across the Arctic. Rates of carbon accumulation vary greatly between the sites, illustrating the importance of local vegetation communities, hydrology and permafrost dynamics. Multiproxy data elucidate the palaeoecology of S. lindbergii and show that it indicates wet conditions in peatlands. We thank Dale Vitt and Adam Hölzer for helping us identify Sphagnum and brown moss species. We thank Julie Loisel and one anonymous reviewer for their constructive comments that considerably improved the quality of the manuscript. G.T.S. acknowledges the Worldwide University Network (WUN) for funding fieldwork in Abisko (Project: Arctic Environments, Vulnerabilities and Opportunities). G.T.S. thanks Jonathan Carrivick, Clare Woulds and Rachel Wiley for assistance in the field. We acknowledge NERC (UK) Training Grants NE/G52398X/1 to E.J.W. and NE/G52398X/1 to T.E.T. An undergraduate student, Rachel Wiley, was ...